SIMPLE PROOF REQUIREMENTS AS A FORM OF LEGAL PROTECTION FOR CREDITORS FOR LEGAL CERTAINTY: SYARAT PEMBUKTIAN SEDERHANA SEBAGAI BENTUK PERLINDUNGAN HUKUM BAGI KREDITOR UNTUK KEPASTIAN HUKUM - Fajar Adiguna; Mardalena Hanifah (ADHAPER: Jurnal Hukum Acara Perdata, 2026)
This study examines legal certainty in the Indonesian bankruptcy system by analyzing the simple proof requirements and creditor protection mechanisms under Law Number 37 of 2004. The legal issues raised are: first, how simple proof requirements affect legal certainty for stakeholders; second, how creditor protection mechanisms balance competing interests in the bankruptcy process. This study uses a normative juridical method with a statute approach, a conceptual approach, and a case approach. The results show that simple proof requirements provide procedural certainty but open up loopholes for abuse that is detrimental to solvent debtors. Creditor protection mechanisms that distinguish between separate, preferential, and concurrent creditors create a hierarchy but often leave commercial creditors with minimal recovery. This study concludes that comprehensive reform is needed to create a bankruptcy system that provides true legal certainty with a balance between creditor rights and business rescue objectives.